2001
DOI: 10.1093/treephys/21.16.1195
|View full text |Cite
|
Sign up to set email alerts
|

Age-related changes in foliar morphology and physiology in red spruce and their influence on declining photosynthetic rates and productivity with tree age

Abstract: The contribution of changes in meristem behavior to age-related decline in forest productivity is poorly understood. We studied age-related trends in needle morphology and gas exchange in a population of red spruce (Picea rubens Sarg.) growing in a multi-cohort stand where trees ranged from first-year germinants to trees over 150 years old, as well as in grafted scions from these trees. In the field study, age-related trends in foliar morphology were determined in six cohorts ranging in age from 2 to 120 years… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

18
103
1
4

Year Published

2003
2003
2021
2021

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 144 publications
(126 citation statements)
references
References 43 publications
18
103
1
4
Order By: Relevance
“…For instance, M A increases 2 to 4-fold from bottom to top of plant canopies (e.g. , with increasing leaf age from developing to fully mature leaves (Hanson et al, 1994;Jurik, 1986;Niinemets et al, 2004) and from seedlings to mature trees (Day et al, 2001;. Among the three bases of expression, E S,FM is discouraged in BVOC studies, because fresh mass is a less stable characteristic than either leaf area or dry mass.…”
Section: Expression Basis Of E Smentioning
confidence: 99%
“…For instance, M A increases 2 to 4-fold from bottom to top of plant canopies (e.g. , with increasing leaf age from developing to fully mature leaves (Hanson et al, 1994;Jurik, 1986;Niinemets et al, 2004) and from seedlings to mature trees (Day et al, 2001;. Among the three bases of expression, E S,FM is discouraged in BVOC studies, because fresh mass is a less stable characteristic than either leaf area or dry mass.…”
Section: Expression Basis Of E Smentioning
confidence: 99%
“…In general, leaf morphology and physiology vary with tree age (Day et al, 2001;Thomas and Winner, 2002;Mediavilla and Escudero, 2003). Furthermore, many previous studies have demonstrated that juvenile age trees may be more sensitive to environmental changes (i.e., temperature, moisture) than mature trees (Howe et al, 2004;Greenwood et al, 2008), with less research focusing on the ecophysiological performances of younger, and smaller life stages (Reinhardt et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, many aspects of leaf morphology and physiology may vary with tree age [11,28]. Comparative studies of different growth stages may provide essential information for understanding the strategies adopted by the species at different stages of their life cycle, as well as the selective pressures that operate in each stage.…”
Section: Introductionmentioning
confidence: 99%